Chronic Fatigue Syndrome - Ridho Berlianto; Arina Widya Murni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Chronic fatigue syndrome is a collection of symptoms characterized by complaints of fatigue that lasts for at least six months or more. It can be accompanied by symptoms of low-grade fever, myalgia, arthralgia, cephalgia, and a sore throat that is sometimes accompanied by enlarged glands. The main psychological symptoms of chronic fatigue syndrome are depression and sleep disturbances. Case Presentation: A 26-year old male patient was treated with a main complaint of feeling tired since 6 months before he was admitted to the hospital. The patient claimed that he was unable to do activities independently because he experienced extreme tiredness. He also complained of a headache that was felt when under stress and was not relieved by rest along with a stabbing-like pain that moved around throughout his body, which also does not decrease with changes in position or rest. He also has heartburn felt since 4 months ago when eating spicy foods, eating late, and especially when experiencing mental stress, which often was accompanied by nausea and vomiting. The results of his physical, laboratory and supporting examinations were all within normal limits. The patient was then diagnosed with chronic fatigue syndrome and functional dyspepsia. Conclusion: Approaches to medical treatment of chronic fatigue syndrome can be done based on general treatment of physical and psychological symptoms experienced. In these circumstances, antidepressant drug therapy and psychotherapy such as cognitive behavioral therapy is needed. In addition, rehabilitation therapy may also be necessary because several studies show that gradual physical exercise yield significant improvement in chronic fatigue syndrome patients.